KAJIAN HADITH TENTANG SALAM DALAM BUKU FIQIH LINTAS AGAMA (FLA) - Syofrianisda Syofrianisda (IAIN Kediri, 2017)
The background of this study is based on hadith riwayah of Muslim through Abu Hurairah about the Prophetâ€™s prohibition to start saying salam to Jewish and Christian people. â€œDonâ€™t start to say salam to Jewish and Christian people. If you greet one of them on the street, urge him to the sideâ€. This hadith is understood by some writers showing the hard, cruel and frightening side of Islam. Moreover, they reject and abandon the hadithâ€™s validity. They argue that this hadith is not suitable with the Islamic foundation that stresses on peace. The writer is interested in discussing this problem since there is no in depth study on some writersâ€™ understanding especially in greeting to non-muslim. Besides, Hartono Ahmad Jaiz has been criticized their idea through books Preventing the Dangerous of Liberal Islamic Network (JIL) and Inter Faith Fiqh (FLA). However, Hartono seems to focus on pluralism verses only. Meanwhile, in tradition of his understanding, he often comments more on hadith related to interfaith problem. Therefore, this thought is strongly possible to develop in the future. It is proved by the development of pluralism study recently. Keywords: Hadith, salam, interfaith fiqh